2020
DOI: 10.1038/s41598-020-71777-2
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiodic manipulation modulates the innate and cell mediated immune functions in the fresh water snake, Natrix piscator

Abstract: Objectives of the current work were to investigate the role of photoperiod and melatonin in the alteration of immune responses in a reptilian species. Animals were kept on a regimen of short or long days. Blood was obtained and leucocytes were isolated to study various innate immune responses. Lymphocytes were separated from blood by density gradient centrifugation and were used to study proliferation. Respiratory burst activity was measured through nitrobluetetrazolium reduction assay while nitric oxide produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 68 publications
0
8
1
Order By: Relevance
“…In the present study, the number of leucocytes was elevated during winter. In contrast, we previously found that short photoperiod suppresses leucocyte number in N. piscator 16 . The disparity in the results may be attributed to the differential effect of photoperiodic modulation in this species.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…In the present study, the number of leucocytes was elevated during winter. In contrast, we previously found that short photoperiod suppresses leucocyte number in N. piscator 16 . The disparity in the results may be attributed to the differential effect of photoperiodic modulation in this species.…”
Section: Discussioncontrasting
confidence: 77%
“…So far non-mammals are concerned, a few studies on the modulation of immune surveillance by blood cells have been performed in fish where significant annual rhythm has been reported in many immune parameters 14 , 15 . In an earlier study, we found circadian and seasonal alterations in nine immune parameters of splenic macrophages in N. piscator 16 . Reptiles are crucial heterotherms because of their significant phylogenic position and N. piscator is a potent contender for studies regarding vertebrate seasonality.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…However, the entrainment of peripheral circadian rhythms in immunity and metabolism may be microbiota‐independent in species where metabolic requirements are not circadian, as well as in species where metabolic requirements and pathogen exposure are uncoupled. For example, ectotherms exhibit circadian rhythms in body temperature and activity (Bartell et al, 2004; Oishi et al, 2004; Tawa et al, 2014), and have some level of circadian cycles in metabolism (Roe et al, 2004) and immunity (Singh et al, 2020; Tripathi et al, 2015), but feeding patterns are often not circadian (e.g. for large reptiles such as snakes and crocodiles that are infrequent feeders).…”
Section: Relevance Of Microbial Oscillations To Outstanding Questions...mentioning
confidence: 99%
“…Melatonin ( N -acetyl-5-methoxytryptamine) is an indoleamine derived from tryptophan and produced by several organisms such as animals [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ], bacteria [ 8 , 9 , 10 , 11 ], fungi [ 7 , 12 ] and plants [ 7 , 10 , 13 ]. In mammals, it was discovered in 1958 in the pineal gland where it is synthesized [ 14 ].…”
Section: Introductionmentioning
confidence: 99%